PREVALENCE, ASSOCIATED FACTORS, DRIVERS AND BARRIERS OF SATISFACTION WITH HIV COUNSELLING AND TESTING SERVICES AMONG ADOLESCENT GIRLS AND YOUNG WOMEN ATTENDING MILDMAY HOSPITAL: A MIXED-METHODS CROSS-SECTIONAL STUDY. - Nazziwa, Norah; Ntuulo, Juliet; Mukose , Aggrey; Rubanga , David; Namutundu, Juliana (Student’s Journal of Health Research Africa, 2024)
Background: Uganda faces high HIV/AIDS rates among adolescent girls and young women (AGYW). This study sought to determine the prevalence of satisfaction with HIV counseling and testing services among AGYW. It aimed to identify factors associated with their satisfaction and explored drivers and barriers to their satisfaction with HCT provided at the adolescent and pediatric clinic in Mildmay Hospital. Methodology: A mixed methods cross-sectional study was conducted, 385 AGYW aged 15-24 were obtained through systematic random sampling. Quantitative data on patient satisfaction was collected through exit interviews using a patient satisfaction questionnaire. Modified position regression was conducted to determine factors associated with satisfaction with HCT using STATA version 15 software. Qualitative data was obtained through ten in-depth interviews. Data analysis for this was done by transcribing, coding, and extracting themes manually. Results: The prevalence of satisfaction with HCT services was 86.0%. AGYW who had the following characteristics had a higher prevalence of satisfaction with HCT services; primary as highest level of education (APR= 1.18, 95% CI: 0.70-1.97), age category 23-24 years (APR= 1.19, 95% CI: 0.82-1.70), were single (APR= 0.93, 95% CI: 0.69-1.26) and were students (APR= 1.17, 95% CI: 0.80-1.70). Drivers of satisfaction included a friendly and supportive environment, positive interactions with healthcare professionals, and efficient service delivery. Barriers on the other hand included long waiting times and accessibility challenges. Conclusion: High satisfaction with HCT services was found among AGYW. Paying attention to the barriers to satisfaction as mentioned by respondents can significantly enhance satisfaction as well as the quality of HCT services. Recommendation: The hospital should work towards reducing waiting times, staff communication skills, and providing transportation assistance to AGYW to ensure that they can access the facility whenever they need to. This will help maintain and enhance satisfaction.